Определитель личинок хищнецов (Heteroptera, Reduviidae) Европейской части СССР - Пучков, П.В. (Вестник зоологии, 1981)
The paper presents a key for identifying the larvae of Reduviidae (Heteroptera) in the USSR European part. The key includes more than 30 species. Out of them only Harpactorinae subfamily is partially summarized below.